All Talk, Little Impact: Media Frames and Discursive Strategies of Out-of-School Children in Nigeria - Muhyideen Imam; Umar Ajetunmobi; Abdulmalik Salman (International Journal of Qualitative Research, 2022)
Statistics show that Nigeria has 10.5 million out-of-school children (OOSC), the highest figure in the globe. This study investigated the media frames and framing strategies of OOSC in Punch, Vanguard, and Daily Trust Newspapers. Using qualitative content analysis, the study adopted van Dijk’s Critical Discourse Analysis (CDA) alongside the thematic and episodic positions of Framing Theory. Analysis showed five media frames and six framing strategies for OOSC. For media frames, OOSC were represented as vulnerable and poor victims; silenced voices; children sprouting from state and policy failure; children sprouting from non-state actors’ failure, as well as children in crisis and need of collaborative responses. For framing strategies, we found source avoidance as a means of masking negativity, authoritativeness as a framing strategy, positive self-presentation, and negative other-presentation, apportioning blame, and foregrounding, alongside direct and implied metaphors. Journalists used these representations to frame opinions and influence people’s perceptions of the OOSC menace. The study recommends that media houses always explore ways of actualizing the truth efficacy of news reportage, and write stories about OOSC more thematically.